Prominent renal complications associated with MMACHC pathogenic variant c.80A > G in Chinese children with cobalamin C deficiency - Xiaoyu Liu; Huijie Xiao; Yong Yao; Suxia Wang; Hongwen Zhang; Xuhui Zhong; Yanling Yang; Jie Ding; Fang Wang (Frontiers Media S.A., 2023)
ObjectiveCblC deficiency, the most common cobalamin metabolic abnormality, is caused by pathogenic variants in the MMACHC gene. The renal complications of this disease have been described only in a small number of cases. This study aimed to better delineate renal phenotype and genetic characteristics in Chinese children with cblC defect.MethodsChildren with cblC deficiency who manifested as kidney damage were enrolled. Clinical, renal pathological, and genetic data were reviewed in detail.ResultsSeven cases were enrolled. Ages at disease onset ranged from 9 months to 5 years. All patients presented with hematuria and proteinuria, and 2/7 cases presented with nephrotic syndrome. Renal dysfunction was observed in 4/7 cases. Renal biopsy was performed in 5/7 cases, and all of them had renal thrombotic microangiopathy. Macrocytic anemia was detected in all seven patients. Six out of seven cases had hypertension, and 2/7 cases presented with pulmonary hypertension. Two of them had a mild intellectual disability, and one suffered from epilepsy. Increased urine methylmalonic acid and plasma homocysteine were detected in seven cases, while two patients had normal levels of urine methylmalonic acid at the initial evaluation. After diagnosis, all seven cases were treated with hydroxocobalamin IM. Six cases were followed-up for 3-8 years. After treatments, anemia was the first to be recovered, followed by proteinuria. Renal function recovered after 1 year in two cases, whereas patient 2 progressed to stage 2 chronic kidney disease 13 years after onset. While a case presented with end-stage kidney disease because of late diagnosis, one case died 3 months after disease onset due to giving up treatment. Three MMACHC pathogenic variants c.80A > G (8/14), c.609G > A (4/14), and c.658_660delAAG (2/14) were detected in all seven children.ConclusionMMACHC variant c.80A > G may be associated with prominent renal complications in Chinese cblC patients. Macrocytic anemia and hyperhomocysteinemia are useful clues for patients with hematuria and proteinuria caused by cblC defect. The most frequent renal pathological manifestation is thrombotic microangiopathy. Early diagnosis and treatment resulted in improving renal and hematological signs.